2003
DOI: 10.1103/physrevd.68.063502
|View full text |Cite
|
Sign up to set email alerts
|

Closed string tachyon condensation and worldsheet inflation

Abstract: Closed string tachyon condensation in spacetime generates potentials on the worldsheet that model two-dimensional inflationary cosmology. These models illustrate and elucidate a variety of aspects of inflation, in particular the generation of quantum fluctuations and their back-reaction on geometry. We exhibit a class of Liouville gravity models coupled to matter that can exhibit, for example: (a) pure de Sitter gravity; (b) slow-roll inflation; (c) topological inflation; and (d) graceful exit into an FRW phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 87 publications
2
52
0
Order By: Relevance
“…In [7], it is suggested that condensation of tachyonic twisted modes localized at fixed points of non-supersymmetric orbifolds like C/Z n and C 2 /Z n give rise to deformations of geometries of the background spacetimes. Configurations bringing with localized tachyons are also discussed in many works [8,9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it is suggested that condensation of tachyonic twisted modes localized at fixed points of non-supersymmetric orbifolds like C/Z n and C 2 /Z n give rise to deformations of geometries of the background spacetimes. Configurations bringing with localized tachyons are also discussed in many works [8,9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For completeness, it is worth displaying the full set of equations of motion in the standard 4d parametrization of the metric. This exercise extends to the fluctuations the remarkable parallel between Liouville cosmology in 2d and Einstein cosmology in 4d, observed at the level of homogeneous backgrounds in [2], see equations (2.14). Using the identifications (3.20), the perturbed Hamiltonian and momentum constraint equations for the quadratic effective action (3.7) read…”
Section: Jhep07(2014)053mentioning
confidence: 99%
“…describes 2d gravity around a de Sitter or anti-deSitter background; coupling to matter, one finds two-dimensional versions of the Friedmann equations of cosmology [2]. Thus we have an ideal setting to investigate the structure of gravitational backreaction at the quantum level -there is enough structure in the single spatial dimension to accommodate the inhomogeneous fluctuations that lead to structure formation, while gravity might be under sufficient control that we can hope to track the quantum back-reaction of the metric on the quantum matter fluctuations.…”
Section: Jhep07(2014)053mentioning
confidence: 99%
See 2 more Smart Citations